SOSIALISASI PENTINGNYA TIDAK MEMBUANG AIR BESAR DI SUNGAI (STOP BABS) DI DESA GAMPANG KECAMATAN PRAMBON - Anwar, Shoim (LPPM Universitas PGRI Adi Buana Surabaya, 2017)
Sanitation is the one component of environmental health as intentional behavior for cultivate human hygiene to prevent direct contact with dirt and other hazardous waste material, with the hope to maintain and improve human health. This is because, the environment may play a direct cause influential factor in supporting the outbreak of disease and as factors affecting the course of the disease. All feces is a medium as breeding and seed base of infectious diseases. The impact of the disease is most often caused by defecation to the river is the widespread bacterium Escherichia coli, which can cause diarrhea. After that could be dehydrated, and because of the condition of human body’s down then get other diseases. The river is a very important source of water to support human’s life. Dynamism watersheds are influenced by the weather, river flow characteristics and human behaviour of the people who live around the river banks. As a result of effluent from people behaviour causes disturbance to the ecosystem of the river flow. Starting from the non-fulfillment of water quality 3B standarts (colorless, odorless and non-toxic), reduced numbers of fish and water animals, the emergence of a rundown neighborhood until the emergence of health problems and others, therefore, to KKN-PPM in the field of Environmental Sanitation and Supply water in the village Easy in Subdisrtict Prambon, Sidoarjo, the program will be made by